Electrode foil, method for manufacturing electrode foil, and method for manufacturing wound capacitor

By forming an enlarged section on the surface of the electrode foil and dividing it into multiple slits, the problem of reduced flexibility and elongation of the electrode foil is solved, and smooth winding and high capacitance of the capacitor are achieved.

CN120981871APending Publication Date: 2025-11-18NIPPON CHEMI CON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480021056.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-24
Filing Date
2024-02-21
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

In the prior art, the expansion process of the electrode foil reduces its flexibility and extensibility, making it difficult to bend and wind smoothly. This results in an increase in the diameter of the capacitor element or a decrease in its electrostatic capacitance, affecting the yield of the capacitor.

Method used

By forming an enlarged section on the surface of the electrode foil and dividing it into multiple slits, the slitting process is carried out in multiple steps. An oxide film is formed on the enlarged section to control the depth and proportion of the slits, thereby improving the flexibility and strength of the electrode foil and ensuring smooth winding.

Benefits of technology

This technology enables smooth bending of the electrode foil during winding, avoids core breakage, maintains the electrostatic capacitance and yield rate of the capacitor, and ensures the miniaturization and high capacitance of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120981871A_ABST
    Figure CN120981871A_ABST
Patent Text Reader

Abstract

The invention provides a method for manufacturing an electrode foil which is easy to bend smoothly during winding, and a method for manufacturing a wound capacitor. A method for manufacturing an electrode foil (1) comprises: a surface expansion step (S01) in which a surface expansion part is formed on the surface of a strip-shaped foil; and a dividing step (S03, S06) in which a plurality of cracks (4) for dividing the expanded surface section (3) extend in the width direction of the foil tape. The segmentation steps (S03, S06) are carried out multiple times, so that the depth of the crack 4 is divided into multiple times to advance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a manufacturing method of a wound capacitor, an electrode foil for the wound capacitor, and a manufacturing method of the electrode foil. BACKGROUND

[0002] An electrolytic capacitor is formed by filling a gap with an electrolyte in order to make a dielectric thin film of an anode adhere to an opposite electrode, and includes a non-solid electrolytic capacitor in which an electrolyte is a liquid, a solid electrolytic capacitor in which an electrolyte is a solid, a hybrid electrolytic capacitor in which a liquid and a solid are included as an electrolyte, and a bipolar electrolytic capacitor in which a dielectric thin film is formed on both electrodes.

[0003] These electrolytic capacitors are formed by impregnating a capacitor element in an electrolyte, and the capacitor element is formed by making an anode foil and a cathode foil face each other with a separator interposed therebetween, the anode foil being formed with a dielectric thin film on a valve metal foil such as aluminum, and the cathode foil being formed of a foil of the same kind or another metal.

[0004] As the electrolytic capacitor, in order to achieve both miniaturization and large capacitance, there is a case where a wound capacitor is adopted. The capacitor element of the wound capacitor is formed by making an anode foil and a cathode foil sandwich a separator and overlap each other, and is wound into a cylindrical shape.

[0005] The electrostatic capacitance of the electrolytic capacitor is proportional to the surface area of the dielectric thin film. Generally, a surface enlargement treatment such as etching is performed on the electrode foil of the electrolytic capacitor, and a chemical conversion treatment is performed on a surface-enlarged portion on which the surface enlargement treatment is performed, to have a dielectric thin film with a large surface area. In recent years, in order to further increase the electrostatic capacitance of the electrolytic capacitor, the surface enlargement is further advanced to a deep portion from the surface of the electrode foil.

[0006] PRIOR ART DOCUMENTS

[0007] PATENT DOCUMENTS

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2007-149759 SUMMARY OF THE INVENTION

[0009] PROBLEMS TO BE SOLVED BY THE INVENTION

[0010] In recent years, in order to meet the requirements of high capacitance, miniaturization, and light weight of the electrolytic capacitor, a higher rate of surface enlargement treatment is performed to enlarge the surface area of the electrode foil. However, with this surface enlargement, the area of the dielectric oxide thin film is enlarged and the area of the foil base material is reduced, which results in the electrode foil becoming more fragile or hard. Thus, the flexibility and extensibility of the electrode foil itself are reduced.

[0011] An electrode foil with reduced flexibility and extensibility cannot be deformed into an arc shape, and it is difficult to wind the electrode foil while smoothly bending it. When wound locally, bending stress concentrates, and kinks occur everywhere. In the worst case, the core of the electrode foil breaks.

[0012] If the electrode foil is kinked and wound everywhere, the diameter of the capacitor element increases. Therefore, when the electrostatic capacity of the wound capacitor is to be maintained, the wound capacitor becomes large. Alternatively, when the diameter of the wound capacitor is to be maintained, the electrostatic capacity of the wound capacitor decreases. Otherwise, it is treated as a defective product, and the yield rate deteriorates.

[0013] The present application provides an electrode foil that is easily bent smoothly when wound, a manufacturing method of the electrode foil, and a manufacturing method of a wound capacitor, in order to solve the problems of the prior art as described above.

[0014] Means for solving the problem

[0015] To achieve the object, the manufacturing method of the electrode foil of the present embodiment has: an area expansion step of forming an area expansion portion on the surface of a strip-shaped foil; and a division step of forming a plurality of cracks that divide the area expansion portion, and the division step is performed a plurality of times.

[0016] A division process interval film forming step of forming an oxidation film on the area expansion portion between any of the division steps of the plurality of times can be provided.

[0017] The division process interval film forming step can include: a hydration treatment of forming a hydration oxidation film on the area expansion portion, or a chemical conversion treatment of forming a film by applying a voltage, or both.

[0018] A first film forming step of forming an oxidation film on the area expansion portion after the area expansion step and before the first division step can be provided.

[0019] A division process interval film forming step of forming an oxidation film on the area expansion portion between any of the division steps of the plurality of times can be provided, and the hardness of the electrode foil obtained in the division process interval film forming step is higher than the hardness of the electrode foil obtained in the first film forming step.

[0020] Between any of the division steps of the plurality of times, the hardness of the foil before the next division step can be made higher than that of the previous foil.

[0021] It can also be that the hardness of the foil divided in the n-th division step of the plurality of division steps is higher than the hardness of the foil divided in any division step before the (n-1)-th.

[0022] It can also be that, in the division step, the crack having a groove width of 50 μm or less including 0 μm is formed in a state where the foil is flattened.

[0023] It can also be that, in the plurality of division steps, the depth of the crack formed in the division step until the last time is advanced, and a new crack is formed.

[0024] It can also include a chemical conversion treatment that, after the last division step, maintains the crack to be able to open and close, and forms an oxide film on the inner surface of the crack.

[0025] The electrode foil manufacturing method is a manufacturing method of an electrode foil before winding of a capacitor element.

[0026] In addition, in order to achieve the object, the manufacturing method of a wound capacitor of the present embodiment includes a winding step of winding the electrode foil obtained by the manufacturing method.

[0027] In order to achieve the object, the electrode foil of the present embodiment includes: a foil in a strip shape; a face expanding portion formed on a surface of the foil; a core portion that is a remaining portion of the foil other than the face expanding portion; a first crack that divides the face expanding portion, the depth of which is less than 70% with respect to a distance from the surface of the foil to the core portion; and a second crack that divides the face expanding portion, the depth of which is 70% or more with respect to the distance from the surface of the foil to the core portion, the proportion of the first crack is 10% or more and 50% or less, and the proportion of the second crack is 50% or more and 90% or less.

[0028] Effects of the Invention

[0029] By the present invention, a plurality of cracks are largely opened at the time of winding, and winding that is smoothly curved can be performed. BRIEF DESCRIPTION OF DRAWINGS

[0030] Figure 1 (a) is a cross-sectional view along the length direction, Figure 1 (b) is a plan view. Figure 1

[0031] Figure 2 is a flow of manufacturing steps of forming a crack of an electrode foil.

[0032] Figure 3 ​is a cross-sectional view of the electrode foil including a crack along the length direction, showing a state after winding.

[0033] Figure 4 (a1) of is a cross-sectional SEM image after the first division treatment in Example 1, Figure 4 (a2) of is a cross-sectional SEM image to which thick lines emphasizing cracks are added. Figure 4 (b1) of is a cross-sectional SEM image after the second division treatment in Example 1, Figure 4 (b2) of is a cross-sectional SEM image to which thick lines emphasizing cracks are added.

[0034] Figure 5 (a1) of is a surface SEM image after the first division treatment in Example 1, Figure 5 (a2) of is a surface SEM image to which thick lines emphasizing cracks are added. Figure 5 (b1) of is a surface SEM image after the second division treatment in Example 1, Figure 5 (b2) of is a surface SEM image to which thick lines emphasizing cracks are added.

[0035] Figure 6 is a photograph of Example 1, Comparative Example 1, and Comparative Example 2.

[0036] Figure 7 (a) of is a photograph of Comparative Example 2 in which the division treatment is performed once, Figure 7 (b) of is a photograph of Example 1 in which the division treatment is performed twice. DETAILED DESCRIPTION

[0037] Hereinafter, embodiments of the electrode foil, the wound capacitor, and the manufacturing method thereof of the present application will be described in detail. Further, the present application is not limited to the embodiments described below.

[0038] (Electrode Foil)

[0039] Figure 1 The electrode foil 1 shown in FIG. 1 is used for an anode foil, a cathode foil, or both of the wound capacitor. The electrode foil 1 can be any one of a low-voltage electrode foil, a medium-high voltage electrode foil, or a high-voltage electrode foil. The electrode foil 1 has a long strip shape using a foil of a valve metal such as aluminum, tantalum, titanium, niobium, and niobium oxide as a base material. A core portion 2 leaving a center in a thickness direction of the electrode foil 1 is formed, and a surface expanding portion 3 is formed on both surfaces of the electrode foil 1. A dielectric thin film 5 is formed on the surface expanding portion 3.

[0040] The surface expanding portion 3 has a porous structure. The porous structure includes a tunnel-like pit, a sponge-like pit, or a gap between dense powders. The core portion 2 is a remaining portion of the electrode foil 1 other than the surface expanding portion 3, or a base material to which metal particles or the like are attached by evaporation, sintering, or the like. In other words, for example, an unetched layer or a base material on which powders are evaporated or sintered corresponds to the core portion 2.

[0041] The dielectric thin film 5 is formed on the uneven surface of the expanded portion 3. The dielectric thin film 5 is typically an oxide thin film formed on the surface layer of the electrode foil 1, and is an aluminum oxide layer that oxidizes the surface of the expanded portion 3 if the electrode foil 1 is an aluminum foil. The dielectric thin film 5 is formed by a hydration treatment and a chemical conversion treatment.

[0042] In the electrode foil 1, a plurality of cracks 4 are intentionally formed on one side or both sides of the expanded portion 3. The cracks 4 are formed before the winding step in which the cathode foil is wound so as to face the cathode foil, and are opened without being blocked before and after the winding step.

[0043] The cracks 4 are openings that split the expanded portion 3. The cracks 4 extend in the tape width direction of the electrode foil 1, and cross the expanded portion 3. It is not necessary to extend in the tape width direction with good accuracy, and it is sufficient that a large number of cracks 4 are in a range of 0 degrees or more and ±45 degrees or less with respect to the tape width direction. The cracks 4 completely cross or partially cross the electrode foil 1, and further, extend continuously or discontinuously.

[0044] The depth of the cracks 4 is not required to reach a level that divides the core portion 2. The depth of the cracks 4 can be any one of a level that does not reach the depth of the core portion 2, a level that reaches the depth of the core portion 2 at the deepest portion, and a level that invades the core portion 2 at the deepest portion. It is not necessary to unify the depths of all the cracks 4.

[0045] It is preferable that the cracks 4 reach the depth of the core portion 2 or invade the core portion 2 at the deepest portion. That is, if the thickness of the expanded portion 3 is 20 μm to 100 μm on a single side, the cracks 4 preferably have a depth of about 20 μm to 100 μm according to the thickness of the expanded portion 3. The deeper the cracks 4 are within a range that does not damage the core portion 2, the better the softness and the extensibility of the electrode foil 1 are imparted. Furthermore, it is possible to suppress buckling or breaking of the core portion 2, and it is possible to suppress a plurality of fine cracks in which unoxidized metal portions are exposed.

[0046] It is further preferable that two kinds of cracks 4 are formed. It is preferable that the first kind of cracks 4 have a depth of less than 70% with respect to the distance from the surface of the electrode foil 1 to the core portion 2, and the second kind of cracks 4 have a depth of 70% or more with respect to the distance from the surface of the electrode foil 1 to the core portion 2.

[0047] Furthermore, it is preferable that the proportion of the first type of crack formed in the electrode foil 1 is 10% or more and 50% or less, and the proportion of the second type of crack is 50% or more and 90% or less. With this type of electrode foil 1, flexibility is achieved by the second type of crack reaching or near the core, and the thickness of the core is ensured by the first type of crack, which is shallower than the second type of crack, thus increasing strength. This results in an electrode foil that achieves a good balance between flexibility and strength, allowing for easy bending and resistance to breakage during winding. Electrode foils outside the range where the proportion of the first type of crack is 10% or more and 50% or less, and the proportion of the second type of crack is 50% or more and 90% or less, may lack sufficient flexibility and strength compared to electrode foils within the range.

[0048] Furthermore, as described later, the slitting step is performed on the electrode foil 1 in multiple steps. By performing the slitting step in multiple steps, compared to a single step, it is easier to control the groove width, groove depth, and the distance between the two ends of a slit 4 to the desired values. This is particularly effective for electrode foils used in medium and high voltage applications with thick dielectric films, low flexibility, and low elongation.

[0049] Furthermore, as described later, the electrode foil 1 is processed in multiple segmentation steps. However, in the initial segmentation step, the average distance between the two ends of a slit 4 is between 40 μm and 150 μm, with short slits being around 10 μm and long slits around 600 μm, and these types of slits coexisting. Preferably, the distance between the two ends of the slit 4 is set to 100 μm or more. The flexibility and elongation of the electrode foil 1 are further improved by using slits 4 with a length of 100 μm or more.

[0050] In the next segmentation step described later, the two ends of a crack 4 are separated by a distance of more than 100 μm on average, and long cracks are a mixture of cracks on the order of millimeters.

[0051] The width of the crack 4 is less than 50 μm, including 0 μm, when the electrode foil 1 is flat without bending. The width of the crack 4 refers to the length along the length direction of the electrode foil 1, measured near the surface of the electrode foil 1. A width of 0 means that the crack 4 is open, but the interfaces of the crack 4 are at least partially connected when the electrode foil 1 is flat without bending.

[0052] Furthermore, the average spacing between adjacent cracks 4 only needs to be less than 2.1 mm, and ideally less than 250 μm. If the average spacing is less than 2.1 mm, the Eriksen value is found to be larger compared to the electrode foil 1 without cracks 4. If the average spacing of cracks 4 is set to less than 250 μm, the Eriksen value becomes exceptionally large.

[0053] (Method for manufacturing electrode foil)

[0054] Figure 2 This is a flowchart illustrating the manufacturing steps involved in forming the crack 4 in the electrode foil 1. For example... Figure 2 As shown, firstly, the surface of the strip-shaped foil is enlarged (step S01). The electrode foil 1 with the enlarged portion 3 is subjected to a hydration treatment as a first thin film formation step (step S02). After the hydration treatment as the first thin film formation step, an initial slitting treatment is performed (step S03). After the initial slitting treatment, a hydration treatment is performed (step S04), followed by a chemical conversion treatment (step S05). The hydration treatment in step S04 and the chemical conversion treatment in step S05 are generally thin film formation steps between the slitting treatments for forming the dielectric thin film. That is, after the chemical conversion treatment in step S05, a further slitting treatment is performed (step S06). Finally, a chemical conversion treatment as a third thin film formation step is performed (step S07).

[0055] In the expansion process of step S01, an expansion area 3 is formed on the electrode foil 1. The expansion process can be electrolytic etching, chemical etching, or sandblasting, or it can involve evaporating or sintering metal particles onto the foil.

[0056] As an example of a method for forming a sintered foil, a slurry in which a metal particle composition is dispersed in a solvent is coated onto a current collector such as a metal foil. Then, the solvent is dried, and the metal particle composition is sintered by heat treatment, thereby forming an electrode layer. The sintering of the metal particle composition based on this heat treatment is called an expansion process, but it is not limited to this. The state of coating a slurry onto a current collector such as a metal foil and drying it is also included in the expansion process.

[0057] Electrolytic etching includes direct current (DC) etching and alternating current (AC) etching, which involves applying a direct current or alternating current to an acidic aqueous solution containing halide ions, such as hydrochloric acid. In medium- to high-voltage applications, where tunnel-like pits are formed, pits are formed by flowing a direct current through an acidic aqueous solution containing halide ions, such as hydrochloric acid, or by flowing a direct current through an acidic aqueous solution such as nitric acid, which enlarges the pit diameter. In chemical etching, the metal foil is immersed in an acidic or alkaline solution.

[0058] In the hydration treatment of step S02, a hydrated oxide film is formed on the expanded portion 3. This hydrated oxide film is also known as a pseudoboehmite layer. If the valve-acting metal is aluminum, then the hydrated oxide film is Al₂O₃·xH₂O. During the hydration treatment, the expanded electrode foil 1 is immersed in pure water at or above 80°C or boiling. The immersion time is determined by balancing the withstand voltage and electrostatic capacitance, based on the target thickness of the hydrated oxide film. Through the hydration treatment, the hardness of the expanded portion 3 increases, making the electrode foil 1 more prone to cracking and less prone to elongation.

[0059] In the slitting processes of steps S03 and S06, the electrode foil 1 is wound around the shaft to propel it forward. The loads applied to the electrode foil 1 differ in steps S03 and S06. Specifically, in steps S03 and S06, at least one of the following is different: roller hardness, roller surface roughness, roller diameter, the wrap angle between the electrode foil 1 entering the roller and the electrode foil 1 exiting the roller, and the tension applied to the stretched electrode foil 1.

[0060] Furthermore, as a difference between the segmentation processes in steps S03 and S06, the initial segmentation process in step S03 is performed after the hydration process in step S02, which is the first thin film formation step. On the other hand, the next segmentation process in step S06 is performed after the hydration process in step S04, which is the thin film formation step between segmentation processes, and the chemical conversion process in step S05.

[0061] At this point, the hardness of the electrode foil before the slitting process in step S06, achieved through the thin film formation step in the slitting process, is preferably harder than the hardness of the electrode foil before the slitting process in step S03. That is, the hardness of the electrode foil before the nth slitting process in multiple slitting processes is preferably higher than the hardness of the electrode foil before any slitting process up to the (n-1)th slitting process. As the electrode foil hardens, there is a tendency for deep cracks to form during the slitting process. However, if the hardness of the electrode foil is too high from the initial slitting stage, there is a risk that the electrode foil will break due to the slitting process. Therefore, by performing the thin film formation step to increase the hardness of the electrode foil in stages and then performing the slitting process, the electrode foil is more prone to cracking and less prone to elongation.

[0062] Furthermore, ideally, the crack 4 is formed on the expansion portion 3 of both sides. However, from the viewpoint of the elongation of the electrode foil 1 during winding, it can be formed at least on the expansion portion 3, which becomes the outer side of the foil and is subjected to tension during the winding of the electrode foil 1.

[0063] In the hydration treatment in step S04 and the chemical conversion treatment in step S05, the hydration treatment in step S04 forms a hydrated oxide film through the same process as in step S02. Then, in the chemical conversion treatment in step S05, the hydrated oxide film is modified by a chemical conversion treatment of around tens of V (above 10V and below 100V) to form a dielectric film 5, such as γ-alumina, which is a crystalline oxide. In the chemical conversion treatment, growth occurs from the boundary surface with the unoxidized valve metal towards both the hydrated oxide film and the valve metal, thus modifying the hydrated oxide film into the dielectric film 5. The chemical conversion treatment in step S07 is the final film formation step, forming the dielectric film 5 on the inner surface of the crack 4 and ensuring the voltage resistance of the electrode foil product. For example, if the product has a medium to high voltage resistance, it is ideal to perform the chemical conversion treatment at a voltage of 200V or higher.

[0064] In this design, the crack 4 is not blocked by the dielectric film 5, and the crack 4 remains in a state where it can be opened and closed. By maintaining the crack in a state where it can be opened and closed, the crack opens first during the winding of the electrode foil. Therefore, stress concentration is less likely to occur in the electrode foil during winding.

[0065] In chemical conversion processing, a voltage is applied to the anode foil in a chemical conversion liquid free of halide ions. The chemical conversion liquid can be a phosphate-based liquid such as ammonium dihydrogen phosphate, a borate-based liquid such as ammonium borate, or an adipic acid-based liquid such as ammonium adipate. The applied voltage simply needs to correspond to the target withstand voltage.

[0066] Furthermore, in the thin film formation step of the splitting process, hydration and chemical conversion treatments may be omitted, and only voltage may be applied. Alternatively, in the thin film formation step of the splitting process, hydration and voltage application may be performed without immersion in the chemical conversion liquid.

[0067] Thus, in the initial slitting stage, there are no cracks 4 that share the bending stress when winding on the roller. Therefore, if a chemical conversion treatment of around tens of V (above 10 V and less than 100 V) is performed before the initial slitting process to increase the hardness of the electrode foil 1 and reduce its flexibility and elongation, the core 2 of the electrode foil 1 is easily bent, and the electrode foil 1 is bent before winding.

[0068] Therefore, before the initial slitting process, the hardness of the expanded portion 3 is slightly increased by hydration treatment, heat treatment, or chemical conversion treatment at around 10V, which is the first thin film formation step S02. This makes the expanded portion 3 easier to crack and prevents the electrode foil 1 from elongating, before the initial slitting process is performed. If the initial slitting process is performed without hydration treatment, which is the first thin film formation step S02, the electrode foil 1 tends to elongate, resulting in a decrease in the electrostatic capacitance of the electrode foil 1.

[0069] Furthermore, if the crack 4 is formed to the target depth during the initial slitting process, a large load needs to be applied to the electrode foil 1, causing the electrode foil 1 to extend. The extended electrode foil 1 has a reduced area expansion rate, and the groove width of the crack 4 increases, thus leading to a decrease in electrostatic capacitance. Therefore, during the initial slitting process, the crack 4 is formed within a range where the electrode foil 1 does not extend. For example, it is sufficient to form a crack 4 with a depth of approximately 50% of the target depth.

[0070] The ideal range for the electrode foil 1 to not elongate is when the elongation rate is approximately 1.0% during the initial slitting process. If the elongation rate exceeds 1.3%, the electrostatic capacitance decreases by more than 1% at the time point of the initial slitting process. Therefore, by adjusting the depth of the crack 4 formed during the initial slitting process, for example by changing the roller diameter, the elongation rate of the electrode foil 1 can be reduced to approximately 1.0% or less.

[0071] Furthermore, with only one slitting process, the crack 4 generated within a range that does not cause the core 2 of the electrode foil 1 to bend or the electrode foil 1 to stretch is shallow, making it impossible to increase the curvature during winding. In other words, it is impossible to tightly wind the electrode foil 1. Therefore, the next slitting process in step S06 is performed to advance the crack 4 in the depth direction.

[0072] In the segmentation process of step S03, the average distance between the two ends of a crack 4 is 40 μm or more and 150 μm or less, with short cracks being about 10 μm and long cracks being about 600 μm, and these types of cracks coexisting. Preferably, the distance between the two ends of the crack 4 is set to 100 μm or more. The flexibility and elongation of the electrode foil 1 are further improved by using cracks 4 with a length of 100 μm or more.

[0073] In the next slicing process in step S06, crack 4 already exists, sharing the bending stress. Therefore, an additional film forming step between slicing processes is added to further increase the hardness of the electrode foil, making it harder than the electrode foil obtained in the first film forming step of step S02. Then, the depth of crack 4 formed in the initial slicing process is advanced to the target.

[0074] In the segmentation process of step S06, not only is the crack 4 advanced in the depth direction, but the intermittent cracks 4 from the initial segmentation process are also connected, and the cracks 4 formed only in a portion are advanced in the width direction of the electrode foil 1. The cracks 4 extending along the width direction improve the suppression effect of new cracks during winding.

[0075] In the segmentation process of step S06, the distance between the two ends of a crack 4 is more than 100 μm on average, and long cracks are a mixture of cracks on the order of millimeters.

[0076] Furthermore, the reason for the decrease in electrostatic capacitance due to the extension of electrode foil 1 is that the width of the groove 4 increases as electrode foil 1 extends. If the width of the groove 4 increases, the surface area of ​​the dielectric film 5 decreases, resulting in a decrease in electrostatic capacitance. If the width of the groove 4 is limited to less than 50 μm, the flexibility and extensibility of electrode foil 1 can be improved by the groove 4, and the decrease in electrostatic capacitance can be suppressed.

[0077] Furthermore, by performing multiple slicing processes, the number of folds generated along the length of the electrode foil 1 is reduced, and the flatness is improved. Therefore, the electrode foil 1 can be tightly wound. Even with the same volume, the electrode foil 1 contained becomes longer, thus increasing the electrostatic capacitance of the wound capacitor.

[0078] Furthermore, by dividing the segmentation process into multiple steps, it is easier to control the groove width, groove depth, and the distance between the two ends of a crack 4 to the desired values ​​compared to a single step.

[0079] Furthermore, the slitting process of the roller can be performed on one or both sides of the electrode foil 1. Additionally, when only one side of the electrode foil 1 is slitting, the orientation of the electrode foil 1 wound on the roller is the same as the orientation of the electrode foil 1 during the winding process for forming a wound capacitor. That is, the inner diameter side and the outer diameter side of the electrode foil 1 are aligned in the same way during the slitting process and during the winding process for forming the capacitor element.

[0080] A preferred form of the roller-based segmentation process is as follows: First, for electrode foil 1, as an initial segmentation process (step S03), after segmenting one side, a segmentation process is performed on the other side. This performs the initial segmentation process on both sides of the electrode foil. Then, a film formation step between the segmentation processes is performed (step S04 and / or step S05), as a second segmentation process (step S06), after segmenting one side, a segmentation process is performed on the other side. Therefore, considering productivity, the method of performing the second segmentation process on both sides of the electrode foil is preferred.

[0081] Furthermore, even without the first film formation step and the inter-segment film formation step, smooth bending is easily achieved during winding by performing multiple segmentation steps. However, by performing the first film formation step and the inter-segment film formation step, the strength of the foil gradually increases, preventing foil bending and making it easier to form deep segmentations. Additionally, even with only the inter-segment film formation step, smooth bending is easier during winding. However, by performing the first film formation step and the inter-segment film formation step, the risk of foil bending is further reduced, and deep segmentations are more easily formed.

[0082] (Wound capacitor)

[0083] A representative example of a wound capacitor is an electrolytic capacitor. Examples of electrolytic capacitors include non-solid electrolytic capacitors in which the electrolyte is a liquid and a dielectric film is formed on the anode foil, solid electrolytic capacitors in which the electrolyte is a solid and a dielectric film is formed on the anode foil, hybrid electrolytic capacitors in which both liquid and solid electrolytes are used, and bipolar electrolytic capacitors in which dielectric films are formed on both the anode foil and the cathode foil.

[0084] A wound electrolytic capacitor is manufactured by housing a capacitor element impregnated with electrolyte in a bottomed cylindrical casing, extending the anode and cathode terminals, sealing it with a sealing body, and then subjecting it to an aging process. The capacitor element is a wound structure formed by overlapping and winding an anode foil and a cathode foil with a separator in between. Electrode foil 1 is used for the anode foil, cathode foil, or both. The separator, made of paper or synthetic fiber, prevents short circuits between the anode and cathode foils.

[0085] Figure 3 This is a schematic diagram showing the state of the wound electrode foil 1 used to form a capacitor element. In this electrode foil 1, multiple slits 4 share and bear bending stress, which is dispersed in each slit 4. The slits 4 are advanced deeply through multiple segmentation processes, and even with a large curvature of winding, the slits 4 open significantly and bend smoothly. Therefore, the stress applied to the electrode foil 1, such as bending or breaking of the core 2, can be suppressed.

[0086] In addition, since the crack 4 is formed by multiple division processes, the elongation of the electrode foil 1 is suppressed, the expansion rate does not decrease, and the groove width of the crack 4 does not increase, thus suppressing the reduction of the electrostatic capacitance of the wound capacitor.

[0087] [Example]

[0088] (Example 1)

[0089] The electrode foil 1 representing this embodiment was fabricated as follows. First, an aluminum foil with a thickness of 120 μm, a width of 10 mm, a length of 55 mm, and a purity of 99.9% by weight or higher was used as the substrate. Then, an enlarged surface area 3 was formed on both sides of the aluminum foil by an enlargement process. Specifically, the aluminum foil was immersed in an acidic aqueous solution containing 1 mol / L hydrochloric acid and 3 mol / L sulfuric acid at a liquid temperature of 70°C, and direct current electrolysis was performed at a current density of 0.50 A / cm² on the substrate. 2 The constant current was applied for approximately 20 seconds. Then, it was immersed in an acidic aqueous solution of nitric acid with a concentration of 1 mol / L, heated to 90°C, for direct current electrolysis at a current density of 0.40 A / cm². 2 The constant current was processed for 90 seconds.

[0090] A hydration treatment was performed on the electrode foil 1 with the expanded portion 3. In the hydration treatment, the electrode foil 1 was immersed in distilled water at 95°C for 30 minutes. This resulted in the formation of a hydrated oxide film on the uneven surface of the expanded portion 3. Following this hydration treatment, an initial slitting process was performed. In the initial slitting process, the electrode foil 1 was... A 6mm shaft is used to press the electrode foil 1 against the shaft, with the encirclement angle of the area where the shaft contacts the electrode foil being 180 degrees. This creates a crack 4 in the expanded area 3. Furthermore, the length of the electrode foil 1 is extended by approximately 1.0% due to the initial sizing process.

[0091] After the initial fractionation treatment, the same hydration treatment was performed again, followed by a chemical conversion treatment. The chemical conversion treatment involved immersion in a 40 g / L boric acid aqueous solution at 95°C, with a flow rate of 0.50 A / cm. 2 A constant current density is applied while a voltage of 30V is applied. After the voltage is applied for about 20 minutes, a dielectric film with a voltage withstand capability of about 30V is formed.

[0092] Following this chemical transformation treatment, a second fractionation process was performed. In this second fractionation process, [the following was observed]: A 10mm shaft is used to press the electrode foil 1 at a 180-degree wrap angle. This causes the crack 4 in the expanded section 3 to penetrate deeper, increasing the length of the crack 4. After the second slicing process, a chemical conversion process is performed again, forming a dielectric film 5 on the inner surface of the crack 4.

[0093] Furthermore, the length of electrode foil 1 is extended by 0.3% to 0.4% after the next slitting process compared to the case without slitting. The length of electrode foil 1 after two slitting processes is extended by 1.37% compared to the case without slitting.

[0094] (Comparative example)

[0095] Electrode foils for Comparative Examples 1 and 2 were prepared in accordance with Example 1. The electrode foil of Comparative Example 1 was not subjected to a slitting process, and no cracks 4 were formed. In Comparative Example 1, after the surface enlargement process, a hydration process and a chemical conversion process were performed. The hydration process and chemical conversion process of Comparative Example 1 were the same as those of Example 1.

[0096] The electrode foil of Comparative Example 2 underwent a single slicing process. A hydration treatment was performed before the slicing process, and a further hydration treatment was performed after the slicing process, followed by a chemical conversion treatment. The slicing process of Comparative Example 2 was the same as the initial slicing process of Example 1. The hydration and chemical conversion treatments of Comparative Examples 1 and 2 were the same as those of Example 1. The length of the electrode foil of Comparative Example 2 after the single slicing process was extended by 0.80% compared to the case without slicing.

[0097] (Observation using a scanning electron microscope (SEM))

[0098] After the initial segmentation process was completed, the cross-section of electrode foil 1 of Example 1 was observed at 350x magnification using a scanning electron microscope. The results are shown below. Figure 4 (a1) and Figure 4 (a2) Figure 4 (a1) is the initial segmented cross-sectional SEM image from Example 1. Figure 4 (a2) adds a thicker line to emphasize crack 4. For example... Figure 4 (a1) and Figure 4 As shown in (a2), in the initial segmentation process, crack 4 did not reach the core 2, but was at a depth of approximately 60% of the core 2. No buckling or fracture was observed in the core 2.

[0099] Furthermore, after the next segmentation process, a cross-section of the electrode foil 1 of Example 1 was observed at 350x magnification using a scanning electron microscope. The results are shown below. Figure 4 (b1) and Figure 4 (b2) Figure 4 (b1) is the cross-sectional SEM image after the next segmentation process in Example 1. Figure 4 (b2) adds a thicker line to emphasize crack 4. For example... Figure 4 (b1) and Figure 5 As shown in (b2), the crack 4, which did not reach the core 2 in the initial splitting process, advances in the depth direction and completely severs the expanded section 3 in the thickness direction, reaching the surface of the core 2 at its deepest point. No buckling or fracture was observed in the core 2.

[0100] Furthermore, after the initial segmentation process, the surface of electrode foil 1 of Example 1 was observed at 150x magnification using a scanning electron microscope. The results are shown below. Figure 5 (a1) and Figure 5 (a2) Figure 5 (a1) is the initial segmented surface SEM image from Example 1. Figure 5 (a2) adds a thicker line to emphasize crack 4. For example... Figure 5 (a1) and Figure 5 As shown in (a2), in the initial slitting process, the crack 4 is shorter than the width of the electrode foil 1, and the straight-line distance between the two ends is approximately 600 μm at most relative to the bandwidth of the electrode foil 1. No bending or breakage was observed in the core 2.

[0101] Furthermore, after the next segmentation process, the surface of electrode foil 1 of Example 1 was observed at 150x magnification using a scanning electron microscope. The results are shown below. Figure 5 (b1) and Figure 5 (b2) Figure 5 (b1) is the surface SEM image after the next segmentation process in Example 1. Figure 5 (b2) adds a thicker line to emphasize crack 4. For example... Figure 6 (b1) and Figure 6 As shown in (b2), in the initial segmentation process, the short cracks 4 advance towards the width direction, the discontinuity decreases, and the continuity increases. Moreover, in a large number of cracks 4, the straight-line distance between the two ends is approximately more than 100 μm relative to the bandwidth of the electrode foil 1, and cracks exceeding the two ends (approximately 800 μm) of the SEM observation field are also observed in the long cracks. Among them, no bending or breakage was observed in the core 2.

[0102] (Softness test)

[0103] One end of each of Examples 1, Comparative Example 1, and Comparative Example 2, which are of the same length and width, was fixed, while the other end was left free. Photographs were taken of Examples 1, Comparative Example 1, and Comparative Example 2 as they sagged due to their own weight. The results are shown below. Figure 7 .exist Figure 7 In the middle, the one closest to the center is the electrode foil 1 of Example 1, the one in the middle is Comparative Example 2, and the one inside is Comparative Example 1.

[0104] Comparative Example 2 underwent one segmentation process, resulting in a crack 4. Therefore, Comparative Example 2 is more curved and droopy compared to Comparative Example 1, which did not undergo segmentation. That is, Comparative Example 2 is more flexible than Comparative Example 1, and its curvature for smooth bending is greater. Example 1 underwent two segmentation processes, resulting in a crack 4 reaching the depth of the enlarged section 3. Therefore, Example 1 is more curved and droopy compared to Comparative Example 2. That is, Example 1 is also more flexible than Comparative Example 2, and its curvature for smooth bending is greater.

[0105] Thus, by performing multiple division processes, the crack 4 penetrates deeper into the electrode foil 1. Moreover, by performing multiple division processes, it was confirmed that the flexibility of the electrode foil 1 increases, allowing the electrode foil 1 to bend smoothly with a greater curvature.

[0106] In addition, Erickson tests were performed on the electrode foil 1 of Example 1 and Comparative Example 2. In the Erickson test, the electrode foil 1 of Example 1, Comparative Example 1, and Comparative Example 2 were clamped at 10 kN using a die (dies) with an inner diameter of 33 mm and an anti-wrinkle plate, and pressed in using a spherical punch and a chisel-shaped punch. The diameter of the spherical punch was 20 mm. The width of the chisel-shaped punch was 30 mm, and its front end, viewed in cross-section, was a spherical surface with a diameter of 4 mm and a radius of 2 mm. The chisel-shaped punch was pressed in orthogonally to the width direction of the electrode foil 1. The pressing speed of the punch was set to 0.5 mm / min.

[0107] The flexibility based on the Erickson test is shown in Table 1 below. Table 1 also records the rate of improvement in flexibility of Example 1 relative to that of Comparative Example 2. Here, the flexibility value is a numerical value defined as the slope of the load change relative to the elongation of the electrode foil 1. If the change in load value relative to elongation is small (if the slope is small), that is, if the flexibility value in the table is small, then it is more gentle (softer) and the electrode foil 1 changes with less force.

[0108] (Table 1)

[0109] As shown in Table 1, it can be confirmed that the flexibility of Example 1 is also improved compared to Comparative Example 2 by the Erickson test. That is, the crack 4 is deeper than that of Comparative Example 2, and the crack 4 extends longer in the bandwidth direction of the electrode foil 1. Therefore, the electrode foil 1 of Example 1 has higher flexibility than that of Comparative Example 2.

[0110] (With or without ruffles)

[0111] Photographs of the long side of Example 1, which underwent two segmentation processes, and Comparative Example 2, which underwent one segmentation process, are shown below. Figure 7 . Figure 7 (a) is a photograph of Comparative Example 2. Figure 7(b) is a photograph of Example 1. ​ As shown in (a), the distance between the two ends of the ruffle in Comparative Example 2 is approximately 8 mm. On the other hand, as... ​ As shown in (b), the distance between the two ends of the pleat in Example 1 is approximately 40 mm. This confirms that the pleat in Example 1 is reduced compared to Comparative Example 2. Furthermore, the distance between the two ends of the pleat, in other words, refers to the distance between the apex of two mountains or the distance between the bottoms of two valleys.

[0112] The flatness near the long side of Example 1 and Comparative Example 2 was measured. Flatness is the ratio of the difference between the surface distance and the straight-line distance between the two ends of the fold along the shape to the straight-line distance between the two ends of the fold. The flatness measurement results are shown in Table 2 below.

[0113] (Table 2)

[0114] As shown in Table 2, the flatness measurement results also confirm that the flatness near the long side of Example 1 is increased compared to Comparative Example 2. Therefore, the electrode foil 1 can be tightly wound, and even with the same volume, the contained electrode foil 1 is longer, thus increasing the electrostatic capacitance of the wound capacitor.

[0115] (Aging assessment)

[0116] A capacitor element was fabricated by winding the electrode foil 1 of Example 1 and the electrode foil of Comparative Example 2 as the anode foil. Aluminum foil was used as the cathode foil. An expanded portion 3 was formed on the cathode foil, but no dielectric film 5 was formed. Cellulose fibers were used in the separator.

[0117] The capacitor element using electrode foil 1 of Example 1 and the capacitor element using electrode foil of Comparative Example 2 are immersed in electrolyte and housed in a bottomed cylindrical outer casing. The anode and cathode terminals are led out and sealed using a sealing body. The electrolyte is a γ-butyrolactone solution of amidine phthalate. Thus, a wound capacitor using electrode foil 1 of Example 1 and a wound capacitor using electrode foil of Comparative Example 2 are manufactured.

[0118] Two manufactured wound capacitors were subjected to an aging process, and the charge required for the aging process was measured. The aging process was carried out at a rated voltage applied at a temperature of 100°C. During the aging process, the change in current flowing between the anode and cathode terminals was measured. Then, the charge (C) was measured when the current value decreased to 30% of the value at the start of the aging process.

[0119] The results of the electricity measurement are shown in Table 3 below. In Table 3 below, the ratio of the electricity of Example 1 to that of Comparative Example 2 is calculated and recorded.

[0120] (Table 3)

[0121] As shown in Table 3, Example 1 consumed less electricity during the aging process compared to Comparative Example 2. This confirms that in Example 1, the crack 4 is deeper than in Comparative Example 2, and the crack 4 extends longer in the bandwidth direction of the electrode foil 1, thus suppressing the formation of fine cracks compared to Comparative Example 2.

[0122] Furthermore, the total elongation during the slitting process of the wound capacitor in Example 1 is greater than that in Comparative Example 2. However, even though the curvature of the wound capacitor in Example 1 is greater than that in Comparative Example 2, it can still be bent smoothly, allowing for the inclusion of a longer electrode foil 1 within the same volume. Therefore, the electrostatic capacitance of the wound capacitor in Example 1 is improved compared to Comparative Example 2.

[0123] (Explanation of reference numerals in the attached image)

[0124] 1: Electrode foil

[0125] 2: Core

[0126] 3: Facial expansion

[0127] 4: Cracks

[0128] 5: Dielectric thin film

Claims

1. A method for manufacturing an electrode foil, characterized in that, have: The expansion step involves forming an expanded area on the surface of a strip of foil; and The segmentation step creates multiple slits that divide the expanded area. The segmentation step is performed multiple times.

2. The method for manufacturing the electrode foil as described in claim 1, characterized in that, The manufacturing method includes a segmentation-inter-process film forming step, wherein an oxide film is formed on the expanded surface between any of the multiple segmentation steps.

3. The method for manufacturing the electrode foil as described in claim 2, characterized in that, The thin film formation step between the segmentation processes includes: The hydration treatment that forms a hydrated oxide film on the expanded surface, or the chemical conversion treatment that forms a film by applying voltage, or both.

4. The method for manufacturing the electrode foil as described in claim 1, characterized in that, The manufacturing method includes a first film forming step, which forms an oxide film on the expanded area after the facetization step and before the initial slitting step.

5. The method for manufacturing the electrode foil as described in claim 4, characterized in that, The manufacturing method includes a segmentation-inter-process film formation step, wherein an oxide film is formed on the expanded surface between any of the multiple segmentation steps. The electrode foil obtained in the segmentation process is made to have a higher hardness than the electrode foil obtained in the first thin film formation step.

6. The method for manufacturing the electrode foil as described in claim 1, characterized in that, Between any of the multiple segmentation steps, the hardness of the foil before the next segmentation step is increased compared to the previous foil.

7. The method for manufacturing the electrode foil as described in claim 1, characterized in that, The foil divided in the nth division step of the multiple division steps has a higher hardness than the foil divided in any of the previous (n-1)th division steps.

8. The method for manufacturing the electrode foil as described in claim 1, characterized in that, In the segmentation step, the cracks are formed with a groove width of less than 50 μm, including 0 μm, while the foil is in a flat state.

9. The method for manufacturing the electrode foil as described in claim 1, characterized in that, In the multiple segmentation steps, the depth of the crack formed in the previous segmentation step is increased, and a new crack is formed.

10. The method for manufacturing the electrode foil as described in claim 1, characterized in that, The manufacturing method includes a chemical conversion treatment, which, after the final segmentation step, maintains the cracks in a manner that allows them to open and close, and forms an oxide film on the inner surface of the cracks.

11. A method for manufacturing a wound capacitor, characterized in that... The method includes a winding step, wherein the winding step involves winding the electrode foil obtained by the manufacturing method of claim 1.

12. An electrode foil, characterized in that... include: Strip-shaped foil; An expanded portion is formed on the surface of the foil; The core portion is the remaining part of the foil excluding the expanded portion. The first type of crack divides the expanded portion, with a depth less than 70% of the distance from the surface of the foil to the core. as well as The second type of crack divides the expanded area with a depth of more than 70% relative to the distance from the surface of the foil to the core. The proportion of the first type of crack is more than 10% and less than 50%. The proportion of the second type of crack is more than 50% and less than 90%.

Citation Information

Patent Citations

  • Method of manufacturing aluminum electrode foil for use of electrolytic capacitor

    JP2007149759A